Biology and chemical composition of Plotosus canius Hamilton, 1822 in the coastal waters of Port Dickson, Malaysia - Usman, Binta Isyaku (2014)
Plotosus canius, the Gray-eel catfish and locally known as “Sembilang or Semilan” in Malaysia, is a popular and well-known marine catfish with high commercial value and usually sold fresh in the markets. Literature on the fish is very scant, and the fish has now been reported to be declining in the wild. The present study was undertaken to investigate the population stock status, fatty acid and amino acid composition,feeding habits, reproductive cycle, sex ratio and fecundity of P. canius in the coastal waters of Kg. Telok, Port Dickson, Peninsular Malaysia between January and December 2012. The samples were collected from the local fishermen of the area during the “full moon” and were immediately stored in ice chest and transported to the laboratory for the various analyses. The data were analyzed using SPSS version 20, Minitab version 16 and FiSAT II software. The length frequency distribution of P. canius implied that the total length ranged from 22.80 to 62.90 cm (mean ± SD, 38.34 ± 8.19 cm) for males and from 24.60 to 60.00 cm (39.06 ± 7.72 cm) for females. There was no significant difference observed between males and females in the size frequency distribution of P. canius (t-test, p > 0.05; Kolmogorov-Smirnov test: dmax = 1.409, p > 0.01). The negative allometric nature of growth was observed in both males (b = 2.707) and females (b =2.879). Analysis of the relationships between TL and various morphometric characteristics of the fish showed that there was strong and significant (R2 > 0.805, p< 0.001) relationship. The length frequency data of P. canius analyzed revealed that asymptotic length (L∞) and growth coefficient (K) were estimated at 67.20 cm and 0.95 yr-1 respectively. The growth performance index (φ’) was calculated as 3.63. Total mortality (Z), natural mortality (M) and fishing mortality (F) were estimated at 2.73 yr-1, 1.43 yr-1 and 1.31 yr-1 respectively. The exploitation level (E) of P. canius was calculated as 0.48. Examination of the stomach fullness revealed that 61.54% of the stomachs contained food at various degrees of fullness, while the remaining (34.46%) were empty. According to index of preponderance (Ip), the stomach contents of P. canius were composed of six major groups viz; fish and fish parts (38.00%), crustaceans (26.69%), molluscs (25.58%), sand and mud (6.68%), debris and detritus (2.99%) and unidentified items (0.06%). In the fish and fish parts group, fish eggs (37.49%) was the dominant food item and this was followed by scales and other partly digested fish parts (0.36%) and small fish (0.15 %) respectively. Among the crustaceans group, Portunus spp was the dominant (1.59%), followed by Neopisserma spp (0.50%), Charabdis spp (0.42%), Acetes spp (0.39%) and Sesarma spp (0.07%). Pholas spp (1.87%) and Anadara spp (1.64%) were the dominant molluscs genera observed in the stomach of P. canius. Examination of the proximate composition of the eggs, juvenile and adult of P.canius revealed that protein ranged between 16.39 and 25.04% (mean = 19.68 ± 4.68%) and fat was in the range of 3.65 and 5.10% (4.68 ± 0.93%). Nine essential amino acids namely; histidine, threonine, valine, methionine, isoleucine, leucine,phenylalanine arginine and lysine were observed in both the eggs, juvenile and adult of P. canius. Saturated fatty acids were the highest (61.62 – 77.25%, 66.95 ± 8.92%) followed by monounsaturated fatty acids (17.57 – 33.82%, 27.92 ± 8.99%), while polyunsaturated fatty acids were the least (4.56 – 5.64%, 5.13 ± 0.53%) in all the eggs, juvenile and adult. The overall sex ratio (males: females) of P. canius was observed to be 1:0.98 and did not differ significantly from the hypothetical ratio 1:1. Analysis of the annual variation of gonadosomatic index (GSI) showed that the major spawning activity in P. canius lasts between May and June in both sexes. 50% of males and females of P. canius were found to mature at sizes between 44 - 48 cm and 40 - 44 cm of total lengths respectively. Fecundity of the fish ranged from 642.26 to 1140.34 (943.05 ± 38.40) eggs per fish. The average fecundity per 1 kg of body weight was found to be 1225.89 eggs, and was established to show positive and significant relationship with body length (R2 = 0.8662, p < 0.05), body weight (R2 = 0.8556, p < 0.05) and ovary weight (R2 = 0.9527, p < 0.05). The mean monthly GSI of females P. canius indicated positive and significant correlation with salinity (r = 0.613; p < 0.05). No significant correlation was observed between the mean monthly GSI and the remaining four variables (temperature, pH, dissolved oxygen and total suspended solids). Overall it could be concluded that P. canius is carnivorous bottom feeder. , The ratio of essential to non-essential amino acids was found to be healthy. The major spawning period was between May and June and the status of exploitation (E = 0.48) was slightly below the optimum level in the coastal waters of Port Dickson,Malaysia.